7 - Politique de financement et gouvernance des universités publiques sénégalaises : vers un nouveau paradigme ? - Mendy, Melyan (Journal of Higher Education in Africa, 2022)
Like most OECD countries in the 2000s, higher education in Senegal, is in the process of undergoing a major change. The Government of the Republic of Senegal has established results-based funding through multi-year performance contracts signed with public universities. Students (past and present) and companies are also asked to contribute funding. In terms of governance, on the one side, the meeting of the university, internal decision-making body, is replaced by the board of directors composed of academics and outsiders representing the world of business, local communities and civil society and chosen for their management skills and their address book. Lasly, the State restructures its institutional relations with the public universities by setting up the executive management of the higher education and the national authority of quality insurance of the higher education.